37.5k views
1 vote
How to get the laplace transform of this equation?

f(t)=t^-3/2

1 Answer

2 votes

Answer:


${L}\{t^(-3/2)}\}$ does not exists

Explanation:

First lets introduce the definition of the Laplace transform (unitary version):


$F(s) = \int\limits_0^\infty {f(t) e^( - st) dt}$;

Let's demonstrate why
${L}\{t^(-3/2)}\}$ does not exists:


$F(s) = \int\limits_0^\infty {t^(-3/2) e^( - st) dt}$

Writing st=u


$F(s) = \int\limits_0^\infty {(u/s)^(-3/2) e^( - u) {du/s}} = \int\limits_0^\infty {(s/u)^(3/2) e^( - u) {du/s}} = s^(1/2) \int\limits_0^\infty {(1/u)^(3/2) e^( - u) {du}} =$

Where:


$\int\limits_0^\infty {(1/u)^(3/2) e^( - u) {du}$

can be written as:


$\int\limits_0^\infty {u^((-1/2)-1) e^( - u) {du} = \Gamma (-1/2)$

Where:


$ \Gamma (z) = \int\limits_0^\infty {u^(z - 1) e^( - u) du} $

Is the Gamma Function

But:


$ \Gamma \left( z \right) $ ; is only defined for z>0

Getting Demonstrated that
${L}\{t^(-3/2)}\}$ does not exists

User IRvanFauziE
by
5.1k points